Workload, social support, and burnout: Testing the mediation effect of work–life balance - Dwi Irma Kurnia; Noermijati Noermijati; Himmiyatul Amanah Jiwa Juwita (Universitas Ahmad Dahlan, 2026)
Critical problems in public sector organizations have arisen due to burnout, driven by limited organizational resources, increasing workloads, and higher performance demands. This study examines the relationship between workload, social support, and burnout, with a focus on the mediating role of work-life balance among Indonesian government employees. A quantitative method was used to collect data through census sampling, involving 235 civil servants at the Central Statistics Agency in Bengkulu, Indonesia. Partial least squares structural equation modeling in SmartPLS was used to analyze the data. The findings reveal two distinct mechanisms leading to burnout. Workload was identified as the primary job demand that significantly increases burnout, both directly and indirectly through reduced work-life balance. In contrast, social support serves as a resource for employment, directly reducing burnout without the mediation of work-life balance. Furthermore, workload negatively affects work-life balance, whereas social support positively influences it. Nevertheless, work-life balance serves only as a mediating variable in the workload–burnout relationship and does not act as a moderator in the social support–burnout relationship. These results empirically support social exchange theory and the job demands–resources model by showing that job resources do not all function through identical mechanisms. In practice, this study suggests that public sector organizations should prioritize strengthening workplace social support and improving workload management to enhance employee well-being and sustainably reduce burnout.